The effect of the som strategy on developing creative thinking and acquiring the art of performing douse skills in the football game - Abdullah, Ahmed (Humanities Journal of University of Zakho, 2023)
The current research aims to reveal the effect of the Som strategy on developing creative thinking and gaining the art of performing suppression skills in the game of football, the researcher used the experimental method using the design of the experimental and control groups with a prior and post test for its suitability to the nature and objectives of the research, as the research community included of the eighth-grade students in the elementary school of Alind of the Directorate of Education of Dohuk Governorate for the academic year 2021-2022, and their number is (143) students divided into four study groups. As for the research sample, the researchers randomly chose group (B and D), (B) The experimental group, and (D) the control group, and the researchers randomly chose 20 students from each group, and thus the total sample of the research became 40 students, homogeneity and equivalence conducted on the research sample in (height, age, mass, some elements of physical fitness, suppression skills), the researcher collected the research data using the Torsen Test for Creative Thinking, which (Kadhim, 2018) by legalizing the scale on the local environment of Iraq and extracted the scientific foundations and its scientific features. In addition to evaluating the art of performing some basic skills in suppression skills, after selecting the sample and conducting homogeneity and equivalence, the researchers applied the experiment for a period of (6) weeks with two teaching units, and the lesson time was (40). The experimental group studied according to the steps of the SUM strategy, while the control group studied according to the adopted method. The researcher used the SPSS statistical program to process the data, and the researcher concluded the following: (Proved the effectiveness of using the SUM strategy for the experimental group and the method followed for the control group in learning the skills of suppression in the game of football, it proved the effectiveness of using the SUM strategy for the experimental group and the method followed for the control group in creative thinking. SUM's strategy was more effective in learning the suppression skills in the football game, as well as developing and improving creative thinking than the adopted method used (for presentation and explanation), which indicates its effectiveness on it).